2018
DOI: 10.3892/mmr.2018.9575
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis to identify key genes and pathways influencing synovial inflammation in osteoarthritis

Abstract: Osteoarthritis (OA) is a chronic arthropathy that occurs in the middle-aged and elderly population. The present study aimed to identify gene signature differences between synovial cells from OA synovial membrane with and without inflammation, and to explain the potential mechanisms involved. The differentially expressed genes (DEGs) between 12 synovial membrane with inflammation and 12 synovial membrane without inflammation from the dataset GSE46750 were identified using the Gene Expression Omnibus 2R. The DEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…There was evidence that Hymovis but not MSCs ameliorated later-stage OA-associated synovial Mmp9 upregulation. MMP9 is one of the key synovitis hub genes recently identified in human OA [50] and known to play a role in nociceptor sensitization [51]. In contrast, MSCs particularly when injected twice slowed the natural post-injury resolution of another of the key OA synovitis hub genes, Il6, which may in part explain their reduced effect on allodynia.…”
Section: Discussionmentioning
confidence: 99%
“…There was evidence that Hymovis but not MSCs ameliorated later-stage OA-associated synovial Mmp9 upregulation. MMP9 is one of the key synovitis hub genes recently identified in human OA [50] and known to play a role in nociceptor sensitization [51]. In contrast, MSCs particularly when injected twice slowed the natural post-injury resolution of another of the key OA synovitis hub genes, Il6, which may in part explain their reduced effect on allodynia.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting the Molecular Targets for OA Differentially expressed genes identified for OA patients were obtained from the Gene Expression Omnibus database (GEO, https://www.ncbi.nlm.nih.Gov/geo/) (Clough and Barrett, 2016). The series GSE46750 (https://www.ncbi.nlm.nih.gov/geo/query/ acc.cgi?acc GSE46750) (Lin et al, 2018) was selected to compare the gene expression profiles of inflammatory I and normal/ reactive (N/R) synoviocytes from the synovium of the same OA patient. Differential expression patterns were identified in two regions of the synovium in 12 patients undergoing total knee arthroplasty.…”
Section: Screening Of Bioactive Components and Molecular Targets Of Bushen Zhuangjin Decoctionmentioning
confidence: 99%
“…Third, several genes such as BMP3 ( He et al, 2018 ), rs1799750 ( Geng et al, 2018 ), and CHI3L1 ( Song et al, 2021 ) show an inhibitory effect on cartilage repair. Fourth, the genes that regulate the expression of inflammatory cytokines in chondrocytes mainly include renin ( Wu et al, 2019a ), ACE ( Wu et al, 2019a ), Ang II ( Wu et al, 2019a ), AT1R ( Wu et al, 2019a ), AT2R ( Wu et al, 2019a ), ATF3 ( Iezaki et al, 2016 ), PTGS2 ( Lin et al, 2018 ; Wang et al, 2020a ), CCL20 ( Lin et al, 2018 ), CHI3L1 ( Lin et al, 2018 ), LIF ( Lin et al, 2018 ), CXCL8 ( Lin et al, 2018 ), and CXCL12 ( Lin et al, 2018 ). Last but not least, COL6A3/ACTG1 ( Li et al, 2020a ) and fibronectin1 (FN1) ( Wu et al, 2020a ) were found involved in fibroblast transformation.…”
Section: Methodsmentioning
confidence: 99%